A Clinic Appointment System with Authentications for Klinik Sejahtera - Azhari, Nur Atikah; Abd Warif, Nor Bakiah (Applied Information Technology And Computer Science, 2023)
The clinic is a health facility for outpatients in indigenous communities. Traditionally, patients need to walk into the clinic or telephone the clinic if they want to do a medical appointment. For this project, Klinik Sejahtera has been chosen as the case study. Klinik Sejahtera located at Parit Raja, Johor. Klinik Sejahtera was using “first come, first serve” to their patients that came on that day. Usually, the appointment will be taken at the counter during the patient’s come to the clinic. The responsible employee at the counter will ask the patient for their identity card and search for the record. They also offer an appointment by contacting the clinic. The problem arises when staff need to record manually and need to remind patient about the appointment. There also have problem with duplication because of too many physical reports. Therefore, this project proposed a clinic appointment system with authentications which is password-based and CAPTCHA. The system will be in web-based. The web-based will be used by the patients, nurses, and doctor. Object-oriented system development is used for the methodology of the proposed system.